Estudio de factibilidad para la creación de una empresa de servicios de limpiezas a viviendas en el cantón Quevedo, año 2014 - Ramos Tinoco, Diana Patricia (2015)
This research was conducted in the Canton Quevedo which has 173575 inhabitants consisted of market research , technical, organizational, economic , and financial evaluation projected 5-year term in order to give the investor a tool support for establishment of a company providing housekeeping households in the canton Quevedo , knowing that there is this kind of service by another company. For registration information, a questionnaire was used to survey the inhabitants of Quevedo Canton criterion to determine its quality and price that they prefer when making use of this service . The net present value had a positive value of $ 202.446.43 which means the liquid return generated by the project updates. Therefore the project is feasible The internal rate of return is 147%, which was higher than the market interest rate, therefore the project is feasible and viable from the economic point of view The cost benefit ratio is determined by dividing net profit for the interest rate of the bank loan, obtaining the target of $ 1.27.